Asymmetric Transformation Driven by Confinement and Self‐Release in Single‐Layered Porous Nanosheets. (7th October 2020) - Sun, Bo; Shen, Bowen; Urushima, Akio; Liu, Xin; Feng, Xiaopeng; Yashima, Eiji; Lee, Myongsoo
Abstract: Reported here is the use of single‐layered, chiral porous sheets with induced pore chirality for repeatable asymmetric transformations and self‐separation without the need for chiral catalysts or chiral auxiliaries. The asymmetric induction is driven by chiral fixation of absorbed achiral substrates inside the chiral pores for transformation into enantiopure products with enantioselectivities of greater than 99 % ee . When the conversion is completed, the products are spontaneously separated out of the pores, enabling the porous sheets to perform repeated cycles of converting achiral substrates into chiral products for release without compromising pore performance. Confinement of achiral substrates into two‐dimensional chiral porous materials provides access to a highly efficient alternative to current asymmetric synthesis methodologies. Abstract : Single‐layer, homochiral porous sheets with induced pore chirality are reported. The porous sheets perform repeatable asymmetric transformations of absorbed achiral substrates without the help of either chiral catalysts or chiral auxiliaries. The porous sheets allow diverse asymmetric transformations, including chiral reduction and chiral macrocyclization in a highly size‐selective and stereospecific way.